Health promotion for the creation of healthy environments in Latin America and the Caribbean - Jorge Coronel Carbo; Nathaly Marzo Páez (Centro Provincial de Información de Ciencias Médicas, 2017)
The promotion of healthy lifestyles comprises the creation of favorable atmospheres as a key activity in the public health, reorientation of health care for the population to guarantee a sustainable development, fight against infectious diseases, malnutrition and unfavorable environmental factors as lack of drinkable water, basic cleaning up and alimentary security; pollution due to industrialization, global warming and risk behaviors as addictions, obesity and others. In several Latin American and Caribbean countries many of the actions to achieve healthy environments are not fulfilled because health education is not sufficiently promoted, so it is imperative to insist one time and another on this matter.